Dosage Adjustment as an Efficiency in Treatment Costs for Chronic Kidney Disease Patients - Kartikawati, Nurfina Dian; Rahmawati, Fita (Journal of Health Economic and Policy Research (JHEPR), 2024)
Introduction: Chronic Kidney Disease (CKD) treatment, in all stages, has been shown to impose a big economic burden. To reduce drug costs, dose adjustment can be used in CKD treatment. Apart from saving costs, dose adjustments can also reduce the risk of side effects due to excessive doses. This research aimed to identify the dose suitability of CKD patient treatment and calculate the difference in treatment costs before and after the dose adjustments. Method: This research was a cross-sectional study using descriptive analysis. Data was collected from medical records in UGM Academic Hospital using purposive nonrandom sampling in inpatient CKD patients with decreased creatinine clearance and serum creatinine who underwent hospitalization for at least one year. Result: There were 58.14% male patients and 41.86% female patients. Most of the patients have stage 5 CKD (46.51%) and hypertension comorbidities (59.30%). Around 69.14% of drugs used in treatment required dose adjustment and only 52.33% of them had appropriate doses based on the Lexicomp Drug Information Handbook. The class of drugs that required the most dose adjustments was antibiotics with 14 occurrences. After the dose adjustment, the saved cost from patients with inappropriate doses was IDR 1,766,330. The biggest cost difference after the dose adjustment was IDR 1,090,865, which comes from the antibiotic group. Conclusion: Dosage adjustments can reduce the incidence of medication errors, improve clinical outcomes, and increase the effectiveness of clinical outcomes and cost-effectiveness.